A methodological proposal for the analysis of a learning practice and a socio-technical system - Latoski, Ariane; Bulgacov, Yara Lúcia Mazziotti; Cunha, Sieglinde Kindl da (Revista de Administração da UFSM, 2019)
This article aims to propose an analytical model and contribute to the methodology used to study the phenomenon of learning and innovation, through the appropriation of two theoretical-methodological models: cultural-historical activity theory (CHAT) and socio-technical system (STS) theory. AIESEC (Association Internationale des Etudiants in Sciences Economiques et Commerciales) Curitiba was used as empirical field to expose such methodology.